2018
DOI: 10.1111/petr.13112
|View full text |Cite
|
Sign up to set email alerts
|

Living‐donor liver transplantation for mild Zellweger spectrum disorder: Up to 17 years follow‐up

Abstract: Mild Zellweger spectrum disorder, also described as Infantile Refsum disease, is attributable to mutations in PEX genes. Its clinical course is characterized by progressive hearing and vision loss, and neurodevelopmental regression. Supportive management is currently considered the standard of care, as no treatment has shown clinical benefits. LT was shown to correct levels of circulating toxic metabolites, partly responsible for chronic neurological impairment. Of three patients having undergone LT for mild Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Yet, after short term effect resulting probably from circulating cells (up to day 5) spontaneous trend to biochemical normalization cannot be excluded as it has been reported in some mild ZSD patients [40]. Compared to LT, HT biochemical impact is reduced in ZSD patients [7].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Yet, after short term effect resulting probably from circulating cells (up to day 5) spontaneous trend to biochemical normalization cannot be excluded as it has been reported in some mild ZSD patients [40]. Compared to LT, HT biochemical impact is reduced in ZSD patients [7].…”
Section: Discussionmentioning
confidence: 90%
“…Based on our experience of dramatic plasma pipecolic acid levels decrease shortly after LT and HT in ZSD patients [7,8], we chose to focus on this biochemical marker for the high dose HT protocol. As previously reported in our ZSD mouse model [18], plasma pipecolic acid levels were increased in ZSD mice.…”
Section: Ht Did Not Modify Plasma Nor Liver Peroxisomal Marker Anomalmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, detailed data of C 27 -bile acid intermediates are missing. 32,33 A possible cause of the liver abnormalities are the C 27bile acid intermediates (ie, DHCA and THCA), which were increased in all patients (in groups 1 and 2). Due to impaired bile acid synthesis, these intermediates accumulate in plasma and organs of ZSD patients.…”
Section: Discussionmentioning
confidence: 98%
“…These studies showed normalization of phytanic acid, pristanic acid, and pipecolic acid in plasma after liver transplantation. Unfortunately, detailed data of C 27 ‐bile acid intermediates are missing …”
Section: Discussionmentioning
confidence: 99%